Three‐dimensional organization of local excitatory and inhibitory inputs to neurons in laminae III–IV of the spinal dorsal horn. (23rd September 2013) - Kato, Go; Kosugi, Masafumi; Mizuno, Masaharu; Strassman, Andrew M.
Key points Axons of sensory neurons that detect painful and non‐painful stimulation of body tissues project centrally to the dorsal horn of the spinal cord, where they are partially segregated in the superficial and deep laminae, respectively. Interneuronal connections between superficial and deep laminae could potentially modulate sensory transmission and contribute to alterations that occur under conditions of pain hypersensitivity. This study used a localized stimulation technique (laser scanning photostimulation) for high‐resolution mapping of local interneuronal synaptic connections to laminae III–IV neurons, combined with intracellular staining for morphological analysis, in an in vitro'slice' preparation of the rat lumbar spinal cord. Synaptic input from superficial laminae (I–II) was received by laminae III–IV neurons with long dorsal dendrites, supporting the idea that interlaminar connectivity is mediated via translaminar dendritic extensions and, more generally, that local connectivity is governed by rules that are specific to the laminar position and morphology of the postsynaptic neuron. Abstract Laser scanning photostimulation was used to map the distribution of the synaptic input zones (sites that give local synaptic inputs) for dorsal horn laminae III–IV neurons, in parasagittal and transverse slices of the rat lumbar spinal cord, and examine how these inputs differed for neurons of different morphologies. All neurons received local excitatory and inhibitory synaptic inputs from within laminae III–IV, while a subset of neurons also received excitatory input from the superficial laminae, especially lamina IIi, as well as the II/III border region. Two anatomical properties were found to be predictive of the dorsoventral position of a neuron's input zone relative to its soma: (1) both excitatory and inhibitory input zones were more dorsal for neurons with longer dorsal dendrites, and (2) excitatory, but not inhibitory, input zones were more dorsal (relative to the soma) for more ventral neurons, with the transition between the dorsal input zones of laminae III–IV neurons and the ventral input zones of lamina II neurons occurring at the II/III border. The observed morphophysiological correlations support the idea that interlaminar connectivity is mediated via translaminar dendritic extensions and that, more generally, local connectivity within the dorsal horn is governed by rules relating the position of a neuron's soma and dendrites to the position of the local presynaptic neurons from which it receives inputs, which are specific to the axis and direction (dorsal vs. ventral), whether the input is excitatory or inhibitory, and the laminar position of the postsynaptic neuron.